Traffic utilization with initial toll: Din Daeng - Klong Toey Expressway - Santoso, Iwan Benyamin; Jones, John Hugh; Prapansak Buranaprapa; Balasubramaniam, A.S.; Carl Duisberg Gesellschaft (CDG) Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1982)
This study investigated the traffic utilization of the Din Daeng - Klong Toey (Port) Expressway from the 29the of October 1981 until the end of January 1982. The travel time needed for vehicles to travel along the expressway was compared with the travel time for vehicles with the same origins and destinations to travel on nearby surface streets over several alternatives routes. with the difference between the characteristics of the expressway and the surface streets, the value of travel time a t break- even points for every possibility route were determined. It was also necessary to study the diver behaviour at the entrance and exit points of this first toll
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Toll roads; Din Daeng -- Klong Toey Expressway